A single exposure to brivaracetam or perampanel does not cause cell death in neonatal rats - Witherspoon, Eric; Zuczek, Nicholas; Williams, Gabrielle; Bernstein, Briana; Ghosh, Anjik; Culjat, Marko; Kaushal, Suhasini; Forcelli, Patrick A. (Frontiers in Pediatrics, 2024)
Introduction Exposure to a range of anti-seizure medications (ASMs) during early brain development adversely impacts neurodevelopmental outcomes in both animal models and in clinical studies. Many ASMs, including phenobarbital, phenytoin, valproate (VPA), and benzodiazepines, are associated with acute neurotoxicity (cell death), impaired synaptic development, and long-term behavioral changes following gestational or neonatal exposure in animals. This is mirrored in clinical studies which show lasting neurodevelopmental deficits following early-life or gestational exposure to these drugs. Brivaracetam (BRV) and perampanel (PER) are two newer generation anti-seizure medications and are of interest based on their mechanisms of action (SV2A modulator, AMPA antagonist, respectively), as other drugs with these mechanisms of action do not trigger acute neurotoxicity. Both BRV and PER show anti-seizure efficacy in developing animals, but potential neurotoxicity of these drugs is unexplored. Methods To address this gap, we treated postnatal day (P)7 Sprague-Dawley rats with BRV (20, 40, 80 mg/kg) and PER (0.1, 0.9, 2.7 mg/kg), and assessed the induction of cell death across a range of vulnerable brain regions 24 h after exposure. Cell death was assessed using pathogreen staining. Results In each of the regions examined (dorsal striatum, nucleus accumbens, motor cortex, cingulate cortex, lateral thalamus, septum, hippocampus), VPA, which served as a positive control, significantly increased cell death as measured by the numer of pathogreen positive cells. By contrast, neither BRV nor PER increased the number of pathogreen positive cells in any region examined. Discussion Our results suggest that BRV and PER may have a positive safety profile–at least with respect to acute induction of cell death - and therefore may offer a safer option for the treatment of early life seizures.